Roles of the Putative Type IV-like Secretion System Key Component VirD4 and PrsA in Pathogenesis of Streptococcus suis Type 2 - Jiang, Xiaowu; Yang, Yunkai; Zhou, Jingjing; Zhu, Lexin; Gu, Yuanxing; Zhang, Xiaoyan; Li, Xiaoliang; Fang, Weihuan (Frontiers in Cellular and Infection Microbiology, 2016)
Streptococcus suis type 2 (SS2) is a zoonotic pathogen causing septic infection, meningitis and pneumonia in pigs and humans. SS2 may cause streptococcal toxic shock syndrome (STSS) probably due to excessive release of inflammatory cytokines. A previous study indicated that the virD4 gene in the putative type IV-like secretion system (T4SS) within the 89K pathogenicity island speciﬁc for recent epidemic strains contributed to the development of STSS. However, the functional basis of VirD4 in STSS remains unclear. Here we show that deletion of virD4 led to reduced virulence as shown by about 65% higher LD50, lower bacterial load in liver and brain, and lower level of expression of inflammatory cytokines in mice and cell lines than its parent strain. The ΔVirD4 mutant was more easily phagocytosed, suggesting its role as an anti-phagocytic factor. Oxidative stress that mimic bacterial exposure to respiratory burst of phagocytes upregulated expression of virD4. Proteomic analysis identified ten secreted proteins of significant differences between the parent and mutant strains under oxidative stress, including PrsA, a peptidyl-prolyl isomerase. The SS2 PrsA expressed in E. coli caused a dose-dependent cell death and increased expression of proinflammatory IL-1β, IL-6 and TNF-α in murine macrophage cells. Our data provide novel insights into the contribution of the VirD4 factor to STSS pathogenesis, possibly via its anti-phagocytic activity, upregulation of its expression upon oxidative stress and its involvement in increased secretion of PrsA as a cell death inducer and proinflammatory effector.